Contribution of Principal Leadership and Academic Supervision to the Performance of Public Elementary School Teachers in Lubuk Basung Subdistrict, Agam Regency - Yeni Wanita; Irsyad irsyad; Yahya Yahya; Rifma Rifma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
This study was motivated by observations made by researchers in public elementary schools in Lubuk Basung District, Agam Regency, which showed that teacher performance was still low. Factors that influence teacher performance include principal leadership and school academic supervision. The purpose of this study was to see: (1) the contribution of principal leadership to the performance of teachers in public elementary schools in Lubuk Basung Subdistrict, Agam Regency, (2) the contribution of academic supervision to the performance of teachers in public elementary schools in Lubuk Basung Subdistrict, Agam Regency, and (3) the contribution of principal leadership and academic supervision to the performance of teachers in public elementary schools in Lubuk Basung, Agam Regency. The method used in this research is quantitative research with a population of 172 teachers.  The sample size was taken using stratified proportional random sampling method, totaling 66 teachers. The instrument in this study used a questionnaire. Data analysis indicates that: (1) the leadership of school principals contributes significantly to the performance of public elementary school teachers in Lubuk Basung District, Agam Regency by 14.1%. (2) Academic supervision significantly contributes to the performance of public elementary school teachers in Lubuk Basung Subdistrict, Agam Regency by 7.3%.  (3) Principal leadership and academic supervision significantly contributed to the performance of teachers of public elementary schools in Lubuk Basung Subdistrict, Agam Regency by 15.1%. This finding can show that the hypothesis can be accepted empirically and the variables of principal leadership and academic supervision are two factors that contribute to the performance of public elementary school teachers in Lubuk Basung Subdistrict, Agam Regency, the remaining 86.9% support outside the two variables studied.